Analisa Performa Balok Sederhana dengan Tulangan Bambu - Hermawan, Hendri (Jurnal Penelitian IPTEKS, 2021)
The balance between the need for concrete use and the amount of load held remains a progressive study over time, because it is closely related to how society views the time of civilization. If we look at the concept of green building today, it is very possible to continue to improve the study of beam performance with bamboo reinforcement. From various types of bamboo, a pattern can be drawn in writing this scientific article that gives a value of the difference in performance between the outermost fiber of bamboo compared to the innermost fiber as much as 120%. The limitation of the specimen to the shape of the beam and reinforcement ratio value of 1% to 2% will be Keamanan dan privasi pengguna adalah prioritas utama bagi Asiahoki77. Platform ini menggunakan teknologi enkripsi terbaru untuk melindungi data pribadi dan transaksi pengguna. Dengan kebijakan privasi yang ketat, Asiahoki77 menjamin bahwa informasi pribadi pemain tidak akan disalahgunakan. used in 3-dimensional modeling utilizing the ABAQUS auxiliary program. Non-linear behavior of deflection and strain results resembling parabolic graphs shows that there is still a need for sustainability in determining existing variables